A Preliminary Study of the Prevalence of Intestinal Parasites in Immunocompromised Patients with and without Gastrointestinal Manifestations (2003)
ABSTRACT: The objective of the present study was to determine the prevalence of the intestinal parasites most commonly found in immunocompromised patients. A group of 111 individuals with acute lymphoid leukaemia (ALL), chronic myeloid leukaemia (CML), human immunodeficiency virus (HIV) and other immunocompromised conditions (principally haematological disorders) was selected. A battery of tests was performed on each individual to identify the presence of parasites (three stool specimens with saline solution and Lugol both directly and by concentration, culture and special staining). No significant differences were found among the frequencies of the different parasites with the several types of immunocompromised conditions. The overall frequencies of potentially pathogenic and opportunistic parasites were 32.4% (36/111) and 9% (10/111) respectively, the most frequently encountered among the latter being Cryptosporidium sp., Microsporidia spp. and Strongyloides stercoralis.